2018
DOI: 10.1101/432294
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Actin dynamics drive microvillar motility and clustering during brush border assembly

Abstract: During differentiation, transporting epithelial cells generate large arrays of microvilli known as a brush borders to enhance functional capacity. To develop our understanding of brush border formation, we used live cell imaging to visualize apical surface remodeling during early stages of this process. Strikingly, we found that individual microvilli exhibit persistent active motility, translocating across the cell surface at ~0.2 μm/min. Perturbation studies with inhibitors and photokinetic experiments reveal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Using a combination of chemical and genetic perturbations to increase or decrease the activity of this motor, we observed striking shortening or elongation of microvilli, respectively ( Figure 6 ). Interestingly, previous studies from our laboratory revealed a similar effect of NM2 inhibition (with blebbistatin) on the nascent microvilli that exhibit robust translocation across the apical surface of LLC-PK1-CL4 kidney epithelial cells early in differentiation ( Meenderink et al. , 2019 ).…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Using a combination of chemical and genetic perturbations to increase or decrease the activity of this motor, we observed striking shortening or elongation of microvilli, respectively ( Figure 6 ). Interestingly, previous studies from our laboratory revealed a similar effect of NM2 inhibition (with blebbistatin) on the nascent microvilli that exhibit robust translocation across the apical surface of LLC-PK1-CL4 kidney epithelial cells early in differentiation ( Meenderink et al. , 2019 ).…”
Section: Discussionmentioning
confidence: 62%
“…Time-lapse analysis of W4 cells treated with 20 µM blebbistatin revealed that microvilli, which normally exhibit striking dynamics on the apical surface (e.g., elongation, shortening, and waving or pivoting around the base), immediately become static and subsequently begin to elongate (Supplemental Movie 3). A previous study from our group established that the parallel actin bundles that support microvilli exhibit robust treadmilling (i.e., retrograde flow), where actin monomer incorporation at tip-oriented barbed ends is balanced by subunit removal from the pointed ends that emerge from the base of these structures ( Meenderink et al. , 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations